Patterns of infection and infectious-related mortality in patients receiving post-transplant high dose cyclophosphamide as graft-versus-host-disease prophylaxis: impact of HLA donor matching - Irene, García-Cadenas (Bone Marrow Transplant, 2020)
Post-transplant cyclophosphamide (PTCy) has become a promising option after allo-SCT, but infections may be more common than in traditional protocols. We herein report 117 consecutive adults who received PTCy-based alloSCT in our hospital: HaploSCT (34%), MRD (19%), and VUD (47%), respectively. The 18-month incidence of severe bacterial, viral, and IFI was 56%, 69%, and 8.7%, without differences between donor type, except for CMV infection and viral hemorrhagic cystitis, which had a higher incidence in the haploSCT cohort (58% vs. 43% and 30% vs. 8% on day +90, p < 0.05). Late infections by conventional respiratory viruses were common in all groups [33/87 (38%)]. The 2-year survival was 72% and did not differ by donor type. IRM at day 30, day 100, and 18 months was 1.7%, 4.4%, and 12%, without differences by donor type (p = 0.7). The primary cause of IRM was bacterial infection (42%). Grade 2–4 acute GvHD was the only independent predictor of IRM. Donor type had no impact on IRM or on survival. In our study, severe infections were common in all donor types using PTCy, with higher rates of early post-engraftment CMV-I and viral HC in haploSCT recipients, although lethal infections were uncommon and similar in all donor types.